Taxonomy of Educational Problems in Support of Readiness for the Implementation of Minimum Competency Assessment and Character Survey in Elementary Schools - Aunurrahman Aunurrahman (STKIP Singkawang, 2020)
This study aims to determine the essential dimensions of primary school education problems in Sintang district based on their types and aspects to analyze the readiness to implement the minimum competency assessment and character survey in 2021 with a focus on two main study dimensions, namely the main problems of education and the dimensions of readiness to implement the minimum competency assessment policy and character survey. The data was collected by combining qualitative and quantitative approaches through the implementation of a Focus Group Discussion (FGD) and a questionnaire. The FGD was attended by supervisors, school principals and elementary school teachers. Meanwhile, the questionnaire was filled in by elementary school teachers who were spread over some elementary schools in several sub-districts of Sintang district. Qualitative data analysis used taxonomic analysis techniques (taxonomy analysis) and interactive analysis from Miles and Huberman. Meanwhile, the quantitative analysis uses descriptive statistical analysis. The results showed that the taxonomy of educational problems in supporting the readiness to implement the minimum competency assessment and character survey in elementary schools in Sintang district was seen from the teacher dimensions regarding shortages and uneven distribution. In the curriculum dimension, it is considered that changes are too fast so that it becomes a source of confusion for some teachers, and in the learning process that has not made good use of information and communication technology tools. In the leadership and management dimension, the implementation of discipline and transparency is still low. In the dimension of school readiness towards implementing minimum competency assessment policies and character surveys in 2021, especially concerning the principal who not yet optimal initiative to encourage teacher involvement to find out and explore new policies and less proactive teachers in seeking information or increasing knowledge related to minimum competency assessment policies and character surveys through various available sources of information.